Pengontrolan Diri Kaum Remaja dengan Pengamalan Thariqat Qodiriyah Naqsyabandiyah di Kabupaten Bandung - Wasik, Abdul (Hanifiya: Jurnal Studi Agama-Agama, 2020)
This article is based on the rise of radical Islamic movements, terrorism, and the youth movement for young people. In addition to these symptoms, it turns out that there are movements of young people who take Sufism's path through the teachings of the Sufi order at the Alwi Mosque, Bandung Regency. With a qualitative approach, this sociological research finds youths who practice the Sufi order's instructions solidly. They carry out religious deepening and soul purification by carrying out various kinds of Sufi order worship. Departing from this, this research discusses the philosophical foundation of young people following the Sufi order, young people's activities when they have a relationship, and the benefits during their development. The results showed that young people who follow Sufi order tend to have a pragmatic instrumental philosophical foundation (al-Zarai'iy), and the Tariqat Qodiriyah Naqshabandiyah performance does not differentiate between young and old. However, at least five benefits for young people to follow the Sufi order: murshid guidance, adding siblings, togetherness, and solidarity, avoiding religious deviations, and being more self-controlled.